Effects of linear and branched side chains on the redox and optoelectronic properties of 3, 4-dialkoxythiophene polymers. Issue 12 (21st February 2020) - Ochieng, Melony A.; Ponder, James F.; Reynolds, John R.
Abstract : Identification of relevant structure–property relationships on solution-processable conjugated polymers have been shown to improve the performance of various redox properties. Abstract : Identification of relevant structure–property relationships on solution-processable conjugated polymers have been shown to improve the performance of various redox active devices. While most research efforts have focused on the conjugated backbone, less focus has been given to the relative impact of side chain structure. Here, we report a side chain variation study tuning the optoelectronic properties on a series of 3, 4-dioxythiophene-based polymers with a common conjugated backbone and differing alkyl side chains. Using a range of analysis methods, it was determined that changing from linear to branched alkyl side chains affects ionization potential, optical bandgap, perceived color, electrochromic contrast, switching speed, and switching stability. Specifically, the polymers with branched side chains have higher onsets of oxidation and optical bandgaps, and demonstrate sudden coloration change compared to polymers bearing linear side chains. This work provides a foundation for establishing structure–property relationships on the effects of alkyl side chains on the next generation of electrochromic conjugated polymers.